PELATIHAN DAN PENDAMPINGAN UMKM PENGRAJIN TENUN DI DESA KARANGREJO PURWOSARI PASURUAN - Susi Ratnawati; Ika Devy Pramudia; Ayes Sandro Alfinero (Seandanan: Jurnal Pengabdian Pada Masyarakat, 2021)
Karangrejo Purwosari Pasuruan Village seeks to find business potential for its people there, especially among the new generation. Gutehan Hamlet is located in Karangrejo Village and Karangrejo Village itself has three Hamlets. So apart from Gutehan, ot her hamlets are named, Krajan and Karangtengah. Already in the early 30s in this village was part of weaving craftsmen, then masui in the 60s the community began to move from weaving to doormats and until now the most important thing is the doormat craftsmen. Not only doormats in the sense of cleaning feet, but also fabric loyalties for mopping and for cleaning households are also produced in this village. However, there are many problems faced by some residents who are involved in this business. Some of these problems come from the lack of trained human resources in this field, making it difficult for residents there to continue the learning and manufacturing process. Apart from that it comes from the factor of public awareness, the community is less aware of what it means that this is a cultural heritage that must remain and must be preserved. Many youths who run to the city choose to work as factory workers rather than in this business which, if calculated, is not inferior to the factory workers' salary, even if the turnover is calculated, it might be more. Then the last, lack of awareness of the importance of legalization and IPR, they think that without legalization and without a brand their business has been successful and they have had enough of it, they are very comfortable with that kind of thing. Several programs are broadly directed at increasing capacity and quality aimed at business actors, both employers and employees or craftsmen. Among other things, socializing to SME entrepreneurs to have a wider capacity through digital marketing. Then socialize to UMKM entrepreneurs about the importance of intellectual property rights and brand rights as an increase in the quality of the business that is currently being engaged.